2013
DOI: 10.1186/1476-4598-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen up-regulates vascular endothelial growth factor expression in prostate cancer cells via an Sp1 binding site

Abstract: BackgroundVascular Endothelial Growth Factor (VEGF) is regulated by a number of different factors, but the mechanism(s) behind androgen-mediated regulation of VEGF in prostate cancer are poorly understood.ResultsThree novel androgen receptor (AR) binding sites were discovered in the VEGF promoter and in vivo binding of AR to these sites was demonstrated by chromatin immunoprecipitation. Mutation of these sites attenuated activation of the VEGF promoter by the androgen analog, R1881 in prostate cancer cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 27 publications
6
57
0
Order By: Relevance
“…Rather a single GC-box in the core promoter is essential for hormone responsiveness of the VEGF promoter [16]. This indicates that the AR is not bound to an ARE binding site, but rather is tethered via a ZFTF, which is bound to the GC boxes (Sp1/Sp3 binding sites) (Figure 1B).…”
Section: Transcription Factors That Regulate Androgen Induction Ofmentioning
confidence: 99%
“…Rather a single GC-box in the core promoter is essential for hormone responsiveness of the VEGF promoter [16]. This indicates that the AR is not bound to an ARE binding site, but rather is tethered via a ZFTF, which is bound to the GC boxes (Sp1/Sp3 binding sites) (Figure 1B).…”
Section: Transcription Factors That Regulate Androgen Induction Ofmentioning
confidence: 99%
“…Indeed, STAT3 is required for VEGF signaling [57]. The relationship between STAT3 and AR in PCa is crucial in modulating VEGF transcription, may be due to the presence of AR-binding sites in the promoter of VEGF gene [58]. Moreover, STAT3-induced HIF1α transcription, which cooperates with STAT3 to induce VEGF expression [59].…”
Section: Role Of Stat3 Signaling In Prostate Cancermentioning
confidence: 99%
“…The prostates of adult rats injected with dehydrotestosterone (DHT) showed a "a four-fold increase in VEGF specific activity" (Sordello et al, 1998). Numerous papers have reported that androgens up-regulate VEGF in cultures of normal and malignant human prostatic cells (Joseph et al, 1997;Sordello et al, 1998;Eisermann et al, 2013).…”
Section: Androgensmentioning
confidence: 97%